2002
DOI: 10.1046/j.1474-8673.2002.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of κ‐opioid receptors in peripheral response to nerve stimulation in κ‐opioid receptor knockout mice

Abstract: 1 The present study aimed to evaluate the role of kappa-opioid receptors at two peripheral sites, the vas deferens and the proximal colon, in kappa-opioid receptor knockout mice. We investigated the role of the kappa-opioid receptor in the vas deferens twitch response and in the colonic "off-contraction", a rebound contractile response which follows the inhibitory response to low frequencies stimulation (10, 20, 30 Hz) and which has been suggested to "locally" reproduce the contractile component of the perista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, these findings are compromised by the lack of specific and reliable antibodies and are yet to be replicated using other technologies. It has been suggested that KOR agonists modulate nonadrenergic noncholinergic mediated "rebound" contractile responses in enteric smooth muscle, but genetic deletion of KOR had no effect on the physiology of these responses (78). Furthermore, the inhibitory effects that the widely used KOR agonist U50-488H has on this system are not blocked by selective KOR antagonism with nor-binaltorphimine, suggesting off-target effects (78).…”
Section: Opioidergic Modulation Of the Enteric Nervous Systemmentioning
confidence: 99%
“…However, these findings are compromised by the lack of specific and reliable antibodies and are yet to be replicated using other technologies. It has been suggested that KOR agonists modulate nonadrenergic noncholinergic mediated "rebound" contractile responses in enteric smooth muscle, but genetic deletion of KOR had no effect on the physiology of these responses (78). Furthermore, the inhibitory effects that the widely used KOR agonist U50-488H has on this system are not blocked by selective KOR antagonism with nor-binaltorphimine, suggesting off-target effects (78).…”
Section: Opioidergic Modulation Of the Enteric Nervous Systemmentioning
confidence: 99%
“…MOR and DOR are both distributed in the submucosal plexus and myenteric plexus, and the activation of MOR and DOR suppresses the excitation of enteric neurons by hyperpolarizing them, delays gastric emptying, increases the time of gastrointestinal transit, and suppresses the secretion of water and electrolytes in the intestine. The activation of KOR also inhibits the ENS contractile response, but its inhibition of the GI tract is weaker than that of MOR and DOR [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…But the observations from these studies refl ect the pharmacological effects of endogenous opioids rather than their physiological functions. Use of knockout mice models for opioid receptors in evaluating the physiological role of endogenous opioid peptides in gastrointestinal function is only beginning [81,82] .…”
Section: Endogenous Opioid System Of the Gutmentioning
confidence: 99%